Beauchamp Hall - Steel, Danielle (London : Pan Books, 2018)
An uplifting, inspiring story about taking back control of your life, by the world's favourite storyteller, Danielle Steel. Winona Farmington can't help but feel that life is passing her by, in her backwater Michigan town. She hates her job, her boyfriend won't commit. But she escapes the dreariness of everyday life with her favourite TV show, Beauchamp Hall, an English period drama. When she makes a shocking discovery, Winona knows it's time to make a change and travels to the picturesque English village that's home to the world of Beauchamp Hall, in pursuit of a new adventure.
Keywords: fiction